Enhanced nucleoplasmic Ca2 + signaling in ventricular myocytes from young hypertensive rats. (December 2016) - Plačkić, Jelena; Preissl, Sebastian; Nikonova, Yulia; Pluteanu, Florentina; Hein, Lutz; Kockskämper, Jens
Abstract: Arterial hypertension causes left ventricular (LV) myocyte hypertrophy. Alterations in nuclear Ca 2 + may be involved in regulation of histone acetylation, transcription and hypertrophy. Regulation of nuclear Ca 2 + in hypertension, however, is unknown. Therefore, we elucidated cellular mechanisms underlying nuclear Ca 2 + regulation in LV myocytes from hypertensive versus normotensive rats and evaluated possible consequences for Ca 2 + -dependent regulation of histone acetylation. LV myocytes and myocyte nuclei were isolated from young spontaneously hypertensive rats (SHR) shortly after development of hypertension. Normotensive Wistar-Kyoto rats (WKY) served as controls. Cytoplasmic and nucleoplasmic Ca 2 + transients (CaTs) were imaged simultaneously using linescan confocal microscopy and Fluo-4. LV myocytes and nuclei from SHR exhibited hypertrophy. Cytoplasmic and nucleoplasmic CaTs were increased in SHR. The increase in nucleoplasmic Ca 2 +, however, exceeded the increase in cytoplasmic Ca 2 +, indicating enhanced nuclear Ca 2 + signaling in SHR. Ca 2 + load of sarcoplasmic reticulum and perinuclear Ca 2 + stores was also increased in SHR, while fractional release from both stores remained unchanged. Intranuclear Ca 2 + propagation was accelerated in SHR, associated with preserved density of nuclear envelope invaginations and elevated nuclear expression of nucleoporins and SR-Ca 2 + -ATPase, SERCA2a. Nuclear Ca 2 + /calmodulin-dependent protein kinase II delta (CaMKIIδ) expression was elevated and histone deacetylases exhibited redistribution from nucleus to cytosol associated with increased histone acetylation in SHR. Thus, in early hypertension, there is remodeling of nuclear Ca 2 + handling resulting in enhanced nuclear Ca 2 + signaling. Enhanced nuclear Ca 2 + signaling, in turn, increases nuclear localization and activity of CaMKIIδ driving nuclear export of histone deacetylases and increased histone acetylation. Highlights: Nuclear Ca 2 + signaling was studied in ventricular myocytes from hypertensive rats. Nuclear Ca 2 + signaling was enhanced in early hypertension. Enhanced nuclear Ca 2 + signaling was associated with epigenetic alterations. Enhanced nuclear Ca 2 + signaling may be involved in remodeling in hypertension.